Desıgn And Development Of Web Based Informatıon System At Harum Snack & Cookıes - Mangapul Siahaan; Kelvin Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Harum Snack & Cookies is a business engaged in culinary snacks that has been running for 5 years. The obstacles faced by Harum Snack & Cookies while carrying out its business activities, there is no web-based information system as a representation in the digital world. This research uses applied research solution that aims to solve practical problems in the modern world. The result of this research is a Website Company Profile. The implementation of this research has had many positive impacts where Harum Snack & Cookies owners feel an increase in sales and new customers